Development and clinical assessment of a novel probiotic candy in the prevention of respiratory infections in asthmatic children - Rana Tafrishi; Hamid Ahanchian; Seyed ali Jafari; Abolfazl Pahlevanloo; Hamidreza Kianifar; Mohammadali Kiani; Nasrin Moazzen; Tahereh sadeghi; Peter D. Sly (World Allergy Organization Journal)
Objective: Asthma is the most common chronic disease among children. Upper respiratory infections are often the cause of asthma exacerbation. Studies suggested that spore-forming probiotics can reduce viral infections. This study aimed to determine the effect of spore-forming probiotic Bacillus candy on respiratory illnesses in asthmatic children. Methods & materials: In this randomized trial, 69 children aged 7–11 years with mild intermittent asthma were randomized to receive probiotic candy (containing 1010 CFU probiotic Bacillus coagulans) or placebo candy, daily for 2 months. The primary outcome was the number of viral respiratory infections. Secondary outcomes included salbutamol metered-dose inhaler (MDI) use, oral corticosteroids, school absenteeism, emergency department visits and hospitalizations, and Pediatric Asthma Control Questionnaire (c-ACT). Results: The frequency of symptomatic respiratory illnesses was significantly lower in the probiotic candy group compared to placebo in the first month (0.28 ± 0.45 vs. 0.51 ± 0.50, p = 0.054), the second month (0.08 ± 0.28 vs. 0.41 ± 0.49, p = 0.001) and the total study (0.37 ± 0.54 vs. 0.90 ± 0.73, 0.001). The percent of patients with prednisolone consumption in the probiotic group was lower than the control group (2.9% vs. 14.7%) but did not show a significant difference (p = 0.081) and no difference was seen in the rate of emergency department visits and hospitalization between the 2 groups (both p = 0.254). The use of salbutamol and school absenteeism in the probiotic group was significantly lower than in the control group (p = 0.040 and p = 0.046, respectively. There was no significant difference in the evaluated scores for asthma control (c-ACT) in both probiotic and placebo groups. After the intervention, the difference between the 2 groups has become significant (p < 0.05). Conclusion: Adding spore-forming probiotic candy containing Bacillus coagulans to standard asthma treatments reduced symptomatic respiratory illnesses over two months. Further studies including longer treatment periods are needed before making recommendations for routine use.